5(6t-3)-6(6-t)+99=0

Simple and best practice solution for 5(6t-3)-6(6-t)+99=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(6t-3)-6(6-t)+99=0 equation:


Simplifying
5(6t + -3) + -6(6 + -1t) + 99 = 0

Reorder the terms:
5(-3 + 6t) + -6(6 + -1t) + 99 = 0
(-3 * 5 + 6t * 5) + -6(6 + -1t) + 99 = 0
(-15 + 30t) + -6(6 + -1t) + 99 = 0
-15 + 30t + (6 * -6 + -1t * -6) + 99 = 0
-15 + 30t + (-36 + 6t) + 99 = 0

Reorder the terms:
-15 + -36 + 99 + 30t + 6t = 0

Combine like terms: -15 + -36 = -51
-51 + 99 + 30t + 6t = 0

Combine like terms: -51 + 99 = 48
48 + 30t + 6t = 0

Combine like terms: 30t + 6t = 36t
48 + 36t = 0

Solving
48 + 36t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-48' to each side of the equation.
48 + -48 + 36t = 0 + -48

Combine like terms: 48 + -48 = 0
0 + 36t = 0 + -48
36t = 0 + -48

Combine like terms: 0 + -48 = -48
36t = -48

Divide each side by '36'.
t = -1.333333333

Simplifying
t = -1.333333333

See similar equations:

| g(n)=(n^2+4+2n)(-3n+2)(1) | | B=703x(w/b^2) | | 11x-62=-2x | | 4a+8=6a-9 | | -4x3/4 | | -14+-12+x=-12 | | 6(-6x-10)=-204 | | 1+2.7+4+0.3x=21 | | -5y+18=2-4y+3 | | 4b-b= | | B/16=6 | | -1+2.7+4+0.3x=2 | | 29=184-y | | 137-u=277 | | -10-5r=-3r | | -4(x-3)=9 | | -16t^2+70t+5=0 | | n+15.64=-13.25 | | 137-u=227 | | 3(1+4n)-2(5n+6)=25 | | 8+2(-7)-4(-7)=1-3(-7) | | d-(1/9)=(7/9) | | 129=-w+189 | | z/−2−6≤−2 | | (1-xy)dx+(xy+x^2)dy=0 | | -9+6f=5f | | -u+46=227 | | -26=2+3x+4+x | | a-22+3a=2 | | 4x/(2x^2) | | 9m=10m-8 | | 9/10•15x/3 |

Equations solver categories